Mainstreaming religious moderation in the digital space: an examination of Islami.co web portal in the perspective of jürgen habermas’ communicative rationality - Mukhammad Zamzami; Siti Roisadul; Nisok Muktafi; Abd A'la Zumrotul Mukaffa (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of popular Islamic media in the digital era, associated with an authority shift from traditional to popular religion, has enhanced peoples’ ways of thinking. Ironically, conservative and radical Islamic models have dominated the digital space. Therefore, in response to this phenomenon, this research examines how the mainstreaming strategy of religious moderation is carried out by moderate groups, specifically a non-affiliated Islamic portal called Islami.co, with the tagline “Enlightening and Friendly Islamic Media.” This research also analyzed articles, concepts, and perspectives to determine whether they are in the moderate category using the Jürgen Habermas’ theory of communicative rationality. Furthermore, the essays in the islami.co were analyzed according to three kinds of validity claims, namely truth, accuracy, and honesty. This study concluded that mainstreaming religious moderation through this islami.co’s media significantly impacts the community as a filter from news content or thoughts that do not reflect the Islamic value of mercy to all mankind. Islami.co’s writers continuously endeavor to test conservative-radical Islamic narratives that develop in a society with logical (aqli) and religious (naqli) arguments presented with brief and uncomplicated explanations. The strategy of popular Islamic portals such as islami.co is quite acceptable to middle-class Muslims, as often preached by the fundamentalist groups. Therefore, it is very appropriate to direct islami.co’s target audience to readers from the general public.